Bridging the genetic gulf: a deep dive into neurotransmission, pharmacogenomics, and genetic variations for optimal pain management - Jaeyres Jani; Constance Liew Sat Lin; D. Kamarudin D. Mudin; Rajesh Kumar Muniandy (Neurotak Publishing, 2024)
Pain embodies a complex sensory experience influenced by a medley of biological, psychological, and genetic. Pain perception can be classed into four main categories: nociceptive pain, neuropathic pain, acute pain, and chronic pain. Genetic polymorphisms, which are basically genetic variations in DNA sequences, have a part to play in the neurotransmission pathways associated with pain perception and the ultimate effectiveness of pain management interventions. Learning about the effects of genetics on neurotransmission in pain management offers a fresh viewpoint on individual variations in pain sensitivity, response to treatment, and the development of personalised approaches to pain management. A closer look at the relationship between genetic polymorphisms and neurotransmission provides a better understanding deep down at the genetic level. These chemical messengers, neurotransmitters, help pass signals between nerve cells; they are essential for pain processing and modulation. Differences in genetic makeup in neurotransmitter-related genes could change how these genes express, function, and regulate, thus changing how humans perceive pain and respond to pain management interventions. The conjunction of neurotransmission and pharmacogenomics forms a unique convergence, composing a narrative that discloses the percipient influence of individual genetic differences on neural communication and responses to pharmaceuticals. These genetic variations elaborately construct the molecular architecture supervising neurotransmitter release, receptor interactions, and enzymatic processes within the nervous system. In this review, the convergence of neurotransmission, pharmacogenomics, and genetic variations illuminates a pivotal realm in healthcare. Genetic variations intricately influence neurotransmission pathways, moulding individual responses to pharmacological interventions. This intersection not only underscores the complexity of human biology but also holds the promise of personalised healthcare solutions. Recognising subtle genetic variations in neurotransmission and pharmacogenomics opens the door to precision medicine, tailoring treatments to individual genetic codes and revolutionising our approach to medical care.